2007
DOI: 10.1080/10420150601068376
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen behaviour in electron-irradiated titanium alloys studied by positron annihilation method

Abstract: Measurements of angular distribution of annihilation photons are applied to investigations of hydrogen behavior in annealed, plastically deformed, and irradiated titanium alloys. It is shown that hydrogen interaction with materials becomes more intensive in presence of structural imperfections of deformational and radiation origin. Probable mechanisms of hydrogen interaction with deformational and radiation defects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In [6], it is shown that the vacancy defects become mobile at temperatures higher than 100°С. Therefore, when irradiating, it is necessary to keep the sample temperature lower than the mentioned level, which is basically not difficult to achieve.…”
Section: Methodsmentioning
confidence: 98%
“…In [6], it is shown that the vacancy defects become mobile at temperatures higher than 100°С. Therefore, when irradiating, it is necessary to keep the sample temperature lower than the mentioned level, which is basically not difficult to achieve.…”
Section: Methodsmentioning
confidence: 98%
“…In order to tackle this task, as an objects of the experimental study iodide titanium and a system of Ti-Al alloys (up to 50 at.% Al) were taken [13,17]. For hydrogenation, the original materials were annealed at 900 0 C, deformed by rolling by ε =50%, and irradiated by 50MeV α-particles up to a fluence of 5 10 15 cm −2 .…”
Section: Titanium Alloys Defect Structure Modification By Hydrogen Samentioning
confidence: 99%
“…Therefore, it is necessary to keep the sample temperature not more than the mentioned, which, in principle, is not an intricate problem. The interstitial atoms in these conditions migrate to the sinks and do not have a considerable influence on the investigation results by positron annihilation methods [3,4].…”
mentioning
confidence: 99%
“…Results and discussion. For interpretation purposes of the investigation results the following annihilation parameters were used: F-redistribution of positron annihilation probability between the conductivity and bound electrons, which is extracted from the spectrum of the annihilation radiation angular correlation and the angle F respective to the Fermi momentum [2][3][4]. Kinetics of radiation defects accumulation as a result of the α-particles irradiation of Ti -Ge alloys system was investigated at fluencies of 10 14 ; 3.2×10 14 ; 3.2×10 15 and 10 16 cm -2 .…”
mentioning
confidence: 99%